Дослідження методів визначення лояльності клієнтів та оцінки рівня їх задоволеності - Лейба, Я. А. (ХНУРЕ, 2023)
The work considers the development of a method for determining and unifying customer’s loyalty and satisfaction levels assessment. The concept of this method, the justification of this possibility and the verification of the application of the method on real data are considered. Special attention was paid to the unification of customer’s loyalty and satisfaction levels assessment, which are based on data from questionnaires and feedbacks. Based on the results of research, conclusions were made about the possibility of its use and development prospects.